2018
DOI: 10.1007/s00253-018-9375-9
|View full text |Cite
|
Sign up to set email alerts
|

Global and pathway-specific transcriptional regulations of pactamycin biosynthesis in Streptomyces pactum

Abstract: Pactamycin, a structurally unique aminocyclitol natural product isolated from Streptomyces pactum, has potent antibacterial, anti-tumor and anti-protozoa activities. However, its production yields under currently used culture conditions are generally low. To understand how pactamycin biosynthesis is regulated and explore the possibility of improving pactamycin production in S. pactum, we investigated the transcription regulations of pactamycin biosynthesis. In vivo inactivation of two putative pathway-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…While there is no evidence to negate the possibility that the glycosylation of 3ABA-PtmI may also occur in vivo, one would expect that such unproductive biotransformation would be regulated by negative feedback and/or equilibrium between biosynthetic intermediates. 27 Furthermore, the fact that GlcNAc-3AAP is not directly involved in pactamycin biosynthesis also suggests that additional modifications of the sugar moiety are required before the glycosylated β-ketoacyl product is cleaved from the ACP. These modifications may involve the oxidoreductase PtmN, the aminotransferase PtmA, the carbamoyltransferase PtmB, the deacetylase PtmG, the radical SAM-dependent C-methyltransferases PtmL and PtmM, and/or rearrangement and cyclization to an aminocyclopentitol intermediate by the radical SAM protein PtmC.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no evidence to negate the possibility that the glycosylation of 3ABA-PtmI may also occur in vivo, one would expect that such unproductive biotransformation would be regulated by negative feedback and/or equilibrium between biosynthetic intermediates. 27 Furthermore, the fact that GlcNAc-3AAP is not directly involved in pactamycin biosynthesis also suggests that additional modifications of the sugar moiety are required before the glycosylated β-ketoacyl product is cleaved from the ACP. These modifications may involve the oxidoreductase PtmN, the aminotransferase PtmA, the carbamoyltransferase PtmB, the deacetylase PtmG, the radical SAM-dependent C-methyltransferases PtmL and PtmM, and/or rearrangement and cyclization to an aminocyclopentitol intermediate by the radical SAM protein PtmC.…”
Section: Discussionmentioning
confidence: 99%
“…phosphate on pactamycin production. The same study demonstrated the strong inhibitory effect of inorganic phosphate with the concentration of 5 mM and higher on PA production (Lu et al 2018).…”
Section: Accepted Articlementioning
confidence: 59%
“…Inactivation of ptmF and ptmE genes in S. pactum completely abolished pactamycin production, indicating that PtmE and PtmF are positive regulators which control the expression of the whole pactamycin biosynthetic gene cluster. However, introduction of a second copy of ptmF and ptmE into S. pactum did not affect the pactamycin titer, suggesting the involvement of other systems in controlling the pathway (Lu et al 2018). In addition, the production of pactamycin is affected by inorganic phosphate, presumably through the PhoR-PhoP system.…”
Section: Regulatory System In Pactamycin Biosynthesismentioning
confidence: 97%
“…As observed in many other biosynthetic pathways in Streptomyces, pactamycin biosynthesis may be regulated by a complex regulatory system involving pathway-specific regulatory proteins, which control the transcription of the structural genes, and global regulatory systems. Analysis of the pactamycin biosynthetic gene cluster revealed two putative pathway-specific regulatory genes ptmF and ptmE in the cluster (Lu et al 2018). PtmF contains a DNA-binding winged HTH domain and a putative response regulator that belongs to the Trans_reg_C family (Chinnadurai 2007).…”
Section: Regulatory System In Pactamycin Biosynthesismentioning
confidence: 99%